THE SPORT EDUCATION MODEL ON THE TEACHING OF TRACK AND FIELD IN SCHOOL - Ginciene, Guy [UNESP]; Matthiesen, Sara Quenzer [UNESP] (Univ Fed Rio Grande Do Sul, Escola Educ Fisica, 2017)
The aim of this research was to implement the Sport Education model on the teaching of track and field in school and to know the particularities of that process, using action research. Two categories were found to present the results: (a) Sport Education and the dimensions of content; (b) students as the center of the teaching-learning process. In general, the implementation was appropriate to the Brazilian reality, particularly for providing knowledge on track and field in the three dimensions and encouraging autonomy among students.
Keywords: Physical Education; Sports; Track and field